ACHONOROPLASTIC CAPRINE FOETAL MONSTROSITY WITH ANURY ATRESIA AND SCROTAL HERNIA - JANA, DEBASIS; JANA, MOUSUMI (The Indian Journal of Animal Reproduction, 2023)
Bull Dog foetal monster or achondroplesla along with sorotal hernia atresia  anl and anury in Black  Bengal goat is reported.
Keywords: Aehandtatilesls; bull dog feetus; monster kid; black bengal doe